Border Security: The Role of RIPK3 in Epithelium Homeostasis - Moriwaki, Kenta; Balaji, Sakthi; Chan, Francis Ka-Ming (Frontiers in Cell and Developmental Biology, 2016)
Receptor interacting protein kinase 3 (RIPK3) is a crucial inducer of necroptosis. Its activity is controlled by interaction with other signal adaptors through the “RIP homotypic interaction motif’ (RHIM). Recent studies revealed a critical function for RIPK3 in the maintenance of epithelial tissue integrity. In mice with genetic deficiency of the apoptosis adaptors FADD or caspase 8, RIPK3 promotes necroptotic cell death of epithelial cells, leading to excessive and lethal inflammation. In contrast, when FADD and caspase 8 functions are intact, RIPK3 serves as a protector of intestinal epithelial integrity by promoting injury-induced wound repair. In the latter case, RIPK3 promotes optimal cytokine expression by cells of hematopoietic origin. Specifically, bone marrow derived dendritic cells (BMDCs) have an obligate requirement for RIPK3 for optimal secretion of mature IL-1β and other inflammatory cytokines in response to toll-like receptor 4 (TLR4) stimulation. RIPK3 promotes cytokine expression through two complementary mechanisms: NF-κΒ dependent gene transcription and processing of pro-IL-1β. We propose that RIPK3 functions in different cell compartments to mediate inflammation through distinct mechanisms.